Unlocking the Truth: Exploring the Impacts of Solitary Confinement on Recidivism and the Need for Mental Health Support for Individuals with Mental Illnesses - Silverthorn, Rachel (American journal of criminal justice, 2024)
Past research shows mixed results regarding the effects of solitary confinement on individuals’ mental health and recidivism. This paper aims to add to the existing literature by examining the relationships between 1) solitary confinement and mental health, and 2) solitary confinement and recidivism for individuals with mental illnesses. Utilizing administrative data from corrections facilities in a large Southeastern state, a series of linear regressions were used to examine the effects of solitary confinement on the need for mental health services, while a logistic regression was used to examine the effects of duration of time spent in solitary confinement on recidivism. Results show that need for mental health services differed for those with and without mental illness after time spent in solitary confinement. Results also indicated that longer placements in solitary confinement were associated with need for mental health services after return to the general population. Finally, a small but significant relationship emerged between solitary confinement and recidivism showing longer stays in solitary confinement increased recidivism. Implications for policy and future research are discussed.